THE FORMATION OF PROFESSIONAL MOTIVATION UNIVERSITY STUDENT - Alexey Lukyanov; Tatyana Voronina (Вестник Северо-Кавказского федерального университета)
The article presents a theoretical analysis and empirical study of the professional motivation formation among students. The essence of professional motivation is shown and its components - cognitive, affective and conative - are described. The conditions of its formation associated with the components of professional motivation, content and organization of the learning process of students. The results of empirical research on the formation ofprofessional motivation of students are described: the hypothesis, scheme and results of the forming influence are presented. It is proved that the creation of special conditions contributes to the formation of professional motivation of students.